2020
DOI: 10.1111/ppe.12695
|View full text |Cite
|
Sign up to set email alerts
|

Association of screen time and sleep duration among Spanish 1‐14 years old children

Abstract: Background Due to the change in screen time usage in the last decade, there is needed to add more evidence about the relationship of screen time and sleep duration. Objective To assess the association between screen time and sleep duration among Spanish children between 1 and 14 years old. Methods We used data from the 2017 Spanish National Health survey, conducted on a representative sample of the Spanish population. We categorised daily leisure screen time as 0‐59, 60‐119, 120‐179, and ≥180 minutes. We class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
(62 reference statements)
0
6
0
3
Order By: Relevance
“…This recommendation is based on previous research indicating the risks of excessive screen time, such as obesity [6], sleep disorders [7], emotional and behavioral problems [8], impaired vision [9], and academic underachievement [10]. Factors contributing to excessive screen time include child difficulties such as hyperactivity/inattention, emotional symptoms, conduct problems [11], and short sleep duration [12]. In terms of neuropsychiatric and psychological effects, a 2018 review by Lissak G. [13] indicates that excessive screen time correlates with sleep deprivation, depressive symptoms, behaviors related to Attention-Deficit/Hyperactivity Disorder (ADHD), diminished social coping abilities, and craving behaviors like substance dependence.…”
Section: Introductionmentioning
confidence: 99%
“…This recommendation is based on previous research indicating the risks of excessive screen time, such as obesity [6], sleep disorders [7], emotional and behavioral problems [8], impaired vision [9], and academic underachievement [10]. Factors contributing to excessive screen time include child difficulties such as hyperactivity/inattention, emotional symptoms, conduct problems [11], and short sleep duration [12]. In terms of neuropsychiatric and psychological effects, a 2018 review by Lissak G. [13] indicates that excessive screen time correlates with sleep deprivation, depressive symptoms, behaviors related to Attention-Deficit/Hyperactivity Disorder (ADHD), diminished social coping abilities, and craving behaviors like substance dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, firstly American Academy of Pediatarics (AAP) in 2016 and more recently World Health Organization (WHO) in 2019 recommended that those children below 2 years should not be exposed to screens and those from 2 years to 5 years the daily screen time should be limited to 1 h [7,8]. However, the percentages of exceeding 1 h of screen time in 2017 were 40.9% and 66.8% for those children from 1 and 2 years and from 3 to 5 years respectively [9].…”
Section: Introductionmentioning
confidence: 99%
“…78 A Spanish study found that 44% of children aged between 1 and 14 years had over 120 minutes/day of leisure screen time, which was associated with short sleep duration. 79 A study of American teenagers found that screen device usage of 5 or more hours/day resulted in 80% higher odds of inadequate sleep compared to those who did not use devices (odds ratio = 1.79, 95% confidence interval: 1.54, 2.08). 67 Smartphone use in bed was found to be a strong predictor for sleep problems including prolonged sleep latency and short sleep duration in adolescents.…”
Section: Risks Of Increased Digital Screen Timementioning
confidence: 99%
“…Another systematic review of studies in children and adolescents aged 6‐19 years reported significant associations between the presence of a media device in the sleep environment near bedtime and inadequate sleep quality, poor sleep quality, and excessive daytime sleepiness 78 . A Spanish study found that 44% of children aged between 1 and 14 years had over 120 minutes/day of leisure screen time, which was associated with short sleep duration 79 . A study of American teenagers found that screen device usage of 5 or more hours/day resulted in 80% higher odds of inadequate sleep compared to those who did not use devices (odds ratio = 1.79, 95% confidence interval: 1.54, 2.08) 67 .…”
Section: Literature Reviewmentioning
confidence: 99%